Edible Crickets (Orthoptera) Around the World: Distribution, Nutritional Value, and Other Benefits—A Review - Magara, Henlay J. O.; Niassy, Saliou; Ayieko, Monica A.; Mukundamago, Mukundi; Egonyu, James P.; Tanga, Chrysantus M.; Kimathi, Emily K.; Ongere, Jackton O.; Fiaboe, Komi K. M.; Hugel, Sylvain; Orinda, Mary A.; Roos, Nanna; et al. (Frontiers in Nutrition, 2021)
Edible crickets are among the praised insects that are gaining recognition as human food and livestock feed with a potential of contributing to food security and reduction of malnutrition. Globally, the sustainable use of crickets as food or feed is undermined by lack of information on the number of the edible crickets, the country where they are consumed and developmental stage consumed. Furthermore, lack of data on their nutritional content and the potential risks to the potential consumers limits their consumption or inclusion into other food sources. We reviewed published literature on edible cricket species, countries where they are consumed and the stage consumed. We further reviewed information on the nutritional content, the safety of cricket consumption and the sensory qualities of the edible crickets. We also looked at other benefits derived from the crickets which include Ethnomedicine, livestock feed, pest management strategy, their contribution to economic development, livelihood improvement, as food preservatives, music, sports and cultural entomology. Lastly, we reviewed information on the farming on the edible crickets. In this review, we report over 60 cricket species which are consumed in 49 countries globally. Nutritionally, crickets are reported to be rich in proteins, ranging from 55 to 73% and the lipids that vary from 4.30 to 33.44 % of dry matter. The reported amount of polyunsaturated fatty acids (PUFA) is 58% of total fatty acids. Edible crickets contain an appreciable amount of macro- and micro-mineral elements such as calcium, potassium, magnesium, phosphorus, sodium, iron, zinc, manganese and copper. Also, the crickets are rich in the required amount of vitamins such as B group vitamins, vitamins A, C, D, E, and K. Overall, the cricket species examined in this review are safe to be consumed and they display high proximate contents that can replace plant and livestock products. The crickets play valuable roles in contributing to the economies of many countries, livelihoods, medicine and social benefits. This review is expected to promote greater recognition of crickets as a source of food, feed and other benefits in the world and encourage up-scaling by farming them for sustainable utilization.